A successful case of vascular hitch procedure in adulthood: A simpler alternative for the vascular obstruction of the pyelo-ureteral junction - El Abidi Hamza; Ibrahimi Ahmed; Lakssir Jihad; Tariqi Reda; Mikou Mohamed Ali; Boualaoui Imad; El Sayegh Hashem; Nouini Yassine (Urology Case Reports)
Congenital obstruction of the upper urinary tract is often caused by the pyeloureteral junction syndrome, the lower polar vessel being the most common extrinsic etiology.We report on a case that was successfully treated using the Vascular HITCH, an alternative method with lower morbidity than Anderson and Hynes pyeloplasty considered the gold standard procedure.Our objective is to outline the aforementioned method and illustrate its ease of use and possible efficacy in carefully chosen adult patients.A very specific set of patients who meet pre- and post-operative criteria are required for vascular HITCH. The outcomes of this method are encouraging.